The association of animal and plant protein with successful ageing: a combined analysis of MEDIS and ATTICA epidemiological studies. Issue 8 (21st June 2021) - Foscolou, Alexandra; Critselis, Elena; Tyrovolas, Stefanos; Chrysohoou, Christina; Naumovski, Nenad; Sidossis, Labros S; Rallidis, Loukianos; Matalas, Antonia-Leda; Panagiotakos, Demosthenes
Abstract: Objective: The aim of the present study was to investigate the differences between the consumption of plant-based v . animal-based protein-rich diets on successful ageing, as well as to identify the optimal combination of dietary protein intake for facilitating successful ageing in people aged >50 years. Design: A combined analysis was conducted in older adults of the ATTICA and MEDIS population-based cross-sectional studies. Anthropometrical, clinical and sociodemographic characteristics, lifestyle parameters, dietary habits and level of protein intake were derived through standard procedures. Successful ageing was evaluated using the validated Successful Aging Index (SAI) composed of ten health-related social, lifestyle and clinical characteristics. Setting: Athens area and twenty Greek islands. Participants: A total of 3349 Greek women and men over 50 years old. Results: Participants with high consumption of plant proteins were more likely to be male, physically active, with higher daily energy intake, higher adherence to the Mediterranean diet and higher level of SAI ( P < 0·001). Participants with 'Low animal & High plant' and 'High animal & High plant' protein consumption had a 6 and 7 % higher SAI score, respectively, compared with the other participants (P < 0·001). In contrast, 'Low animal & Low plant' and 'High animal & Low plant' protein intake was negatively associated with SAI as compared to the combination of all other consumption categories ( P < 0·02). Conclusions: The consumption of a plant-based protein-rich diet seems to be a beneficial nutritional choice that should be promoted and encouraged to older people since it may benefit both individual's health and prolong successful ageing.